(untitled) (CIPEEX, 2025)
The principle of the reasonable duration of proceedings, based on Article 5, item LXXVIII of the Federal Constitution and Articles 4, 6 and 8 of the Code of Civil Procedure, aims to guarantee the speedy progress of proceedings in a timely manner. In view of the need to guarantee procedural speed and the effectiveness of justice, the question arises as to whether self-composition, as a form of conflict resolution, can be an instrument that makes the principle of reasonable length of proceedings a reality. The general objective of this project is to analyze whether self-composition can be an instrument that makes the reasonable duration of proceedings effective. The following specific objectives have been formulated: i) to discuss the concept and forms of self-composition; ii) to address the principle of reasonable length of proceedings, highlighting its importance for the legal system; iii) to analyze the possibilities and limitations of self-composition as an instrument to guarantee procedural speed and the effectiveness of justice. The methodology of this study will include a bibliographical review to discuss the concept of self-composition and the case law related to the principle of reasonable length of proceedings. Legal works, academic articles and court decisions will be consulted to support the theoretical and practical analysis of the subject. In addition, case studies will be carried out to identify concrete experiences of using self-composition in the search for procedural speed. This project is justified by the importance of discussing alternative forms of conflict resolution that can contribute to the effectiveness of justice. In view of the challenges faced by the judicial system, it is essential to investigate whether self-composition can be an effective tool for guaranteeing the speedy resolution of legal claims, in accordance with the principle of a reasonable length of proceedings. It is hoped that this study will provide a basis for understanding the importance of self-composition as a tool for guaranteeing procedural speed and the effectiveness of justice. In addition, it is hoped that this project will contribute to the development of proposals and strategies to promote self-composition in the judicial system, with a view to improving access to justice and reducing court congestion.